Surgical Site Infection In Laparotomy - Bhatta, Pashupati N.; Yadav, Umesh Kumar; Mishra, Gorakh Nath; Jha, Randhir; Shrestha, Kumar (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Surgical site infection (ssi) is one of the most common surgical complications which increases the rate of morbidity and mortality and increases the health care cost by prolonging the hospital stay. AIMS AND OBJECTIVES: The main objective of the study was to find out the incidence of ssi in emergency laparotomy in general surgery and to find out the associated risk factor for ssi. MATERIAL & METHODS: Study was carried out in national medical college, Birgunj from January 2011 to June 2012 after getting ethical clearance from Institutional Review Committee National Medical College. Total 200 cases were included in study and follow up done up to 30 days postoperatively. RESULTS: Out of 200 patients, 76 patients developed ssi. The total incidence of ssi was 38%.The rate ssi in clean-contaminated, contaminated and dirty wound were 18.2%, 33.3% & 45.5% respectively. Age, type of surgical operation and prolonged duration of surgery were the significant risk factor for ssi while sex, BMI were not statistically significant. The median length of hospital stay with ssi was 16 days while the median length of hospital stay without ssi was 10 days. CONCLUSION: The rate of ssi was found to be higher in our study in comparison to western study but neariy same when comparing to study of Asian countries. so, we emphasize for the need of evidence based infection control and recommend for better surveillance program me for control of ssi in each hospital. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 22-25